A homolog of FHM2 is involved in modulation of excitatory neurotransmission by serotonin in C. elegans. - Elena G Govorunova; Mustapha Moussaif; Andrey Kullyev; Ken C Q Nguyen; Thomas V McDonald; David H Hall; Ji Y Sze (PLoS ONE, 2010)
The C. elegans eat-6 gene encodes a Na(+), K(+)-ATPase alpha subunit and is a homolog of the familial hemiplegic migraine candidate gene FHM2. Migraine is the most common neurological disorder linked to serotonergic dysfunction. We sought to study the pathophysiological mechanisms of migraine and their relation to serotonin (5-HT) signaling using C. elegans as a genetic model. In C. elegans, exogenous 5-HT inhibits paralysis induced by the acetylcholinesterase inhibitor aldicarb. We found that the eat-6(ad467) mutation or RNAi of eat-6 increases aldicarb sensitivity and causes complete resistance to 5-HT treatment, indicating that EAT-6 is a component of the pathway that couples 5-HT signaling and ACh neurotransmission. While a postsynaptic role of EAT-6 at the bodywall NMJs has been well established, we found that EAT-6 may in addition regulate presynaptic ACh neurotransmission. We show that eat-6 is expressed in ventral cord ACh motor neurons, and that cell-specific RNAi of eat-6 in the ACh neurons leads to hypersensitivity to aldicarb. Electron microscopy showed an increased number of synaptic vesicles in the ACh neurons in the eat-6(ad467) mutant. Genetic analyses suggest that EAT-6 interacts with EGL-30 Galphaq, EGL-8 phospholipase C and SLO-1 BK channel signaling to modulate ACh neurotransmission and that either reduced or excessive EAT-6 function may lead to increased ACh neurotransmission. Study of the interaction between eat-6 and 5-HT receptors revealed both stimulatory and inhibitory 5-HT inputs to the NMJs. We show that the inhibitory and stimulatory 5-HT signals arise from distinct 5-HT neurons. The role of eat-6 in modulation of excitatory neurotransmission by 5-HT may provide a genetic explanation for the therapeutic effects of the drugs targeting 5-HT receptors in the treatment of migraine patients.